The effectiveness of nursing intervention on breastfeeding-related problems among nursing mothers in selected primary health clinics in Lagos, Nigeria - Folami F; Ademuyiwa Y; Olowe A (Archives of Nursing Practice and Care - Peertechz Publications, 2018)
Breastfeeding is a vital component of realizing every child's right to the highest attainable standard of health, while respecting every mother's right to make an informed decision about how to feed her baby. Several factors related to the mother and the baby has a negative effect on the duration of exclusive breastfeeding. Most breastfeeding mothers have experienced variety of difficulties because of some of the techniques used. The broad objective of this study is to determine the effectiveness of nursing intervention on breastfeeding-related problems among nursing mothers in selected primary health clinics in Lagos, Nigeria. Three research questions were raised and three hypotheses were generated in line with the objectives. One of the hypotheses raised in the study was that there is no significant difference between the pre and post knowledge level of participant on proper positioning of mother and baby after four weeks of training. One group pretest-posttest of quasi-experimental was used for this study. The study was conducted among mothers of children less than five years who attended the selected Primary Health Care Centers (PHCs) in Oshodi-Isolo LGA for outpatient clinics and immunization. The multistage sampling technique was used. Two hundred and fourteen participants agreed to participate but only 204 showed up for the training given a response rate of 95.3%. The study results showed that immediate nursing intervention towards lactation related problems are very significant in maintaining exclusive breastfeeding. Recommendations were made based on the findings that all pregnant women should be educated on management of breastfeeding related problems prenatally and establishment of breastfeeding support groups should be adopted.